DEIXIS USED IN THE MOVIE “TOY STORY: LAMP LIFE” BY DISNEY - RULIK SETIANI; SINTA NOVIA; SIGIT SUHARJONO (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2024)
This research is a deixis analysis which is one of the sciences of semantics. This study aims to classify deixis, to find the dominant deixis in movie, and to discover is there any deixis that cannot found in the movie. This research use qualitative descriptive strategy as the method. Researchers used a movie from Disney entitled